Breast-feeding: historical aspects of the Brazilian public politics - Michelle Araújo Moreira; Regina Lúcia Mendonça Lopes (Universidade Federal Fluminense, Escola de Enfermagem Aurora de Afonso Costa, 2007)
The politics public Brazilians maids for the breast-feeding moved forward, in spite of the focus to be returned, prioritary for the children, justified for the mortality rate. It was aimed at to rescue the public political principal historical aspects with relationship to the breast-feeding. I study qualitative, descriptive and bibliographical that, it counted as historical cutting the period from 1985 to 2005. The preliminary rising, tends the term to the breast-feeding and the language the Portuguese, it was done in the base of data of Scientific Eletronic Library Online - SciELO, site of Brazil, and they were identified 8 scientific goods. Later, they were read books and master's degree dissertations to have the thematic breast-feeding. During the analysis, we noticed that the actions in breast-feeding moved forward in the decade of 80, and that the scientific production was more strengthened in São Paulo. It is necessary that the subjects shimmer the breast-feeding as a changeable historical process, and that the scientific production involves factors social, political, economical, cultural and existential. Key words: formulation of politics; breast-feeding; the woman's health.